Peran Ekonomi Informal Berbasis Platform WhatsApp dalam Menjaga Ketahanan Pendapatan Keluarga Pedesaan Selama Krisis Pandemi - Muammar, Muhammad Muwafiqul; Fuadi, Muhammad Syahrul (Universitas Nahdlatul Ulama Blitar, 2021)
The COVID-19 pandemic has placed significant pressure on the incomes of rural families, particularly those dependent on the informal economy. This study aims to analyze the role of the WhatsApp-based informal economy in maintaining rural family income resilience during the pandemic crisis. The study used a mixed methods empirical approach, conducted in three rural villages in East Java. Quantitative data were obtained through a survey of 300 households operating informal businesses, while qualitative data were collected through in-depth interviews and focus group discussions. The results indicate that the use of WhatsApp for marketing, order acceptance, and distribution coordination contributes positively to household income maintenance. The intensity of WhatsApp use has been shown to be significantly associated with family income resilience during the pandemic. However, this role is complementary and still faces limitations in scale, capital, and social protection. This study emphasizes the importance of simple digital assistance and policy support to strengthen the economic resilience of rural families.